A High Throughput Cell-Based Screen Assay for LINE-1 ORF1p Expression Inhibitors Using the In-Cell Western Technique - Yanni Kou; Shujie Wang; Yanjie Ma; Ning Zhang; Zixiong Zhang; Qian Liu; Yang Mao; Rui Zhou; Dongrong Yi; Ling Ma; Yongxin Zhang; Quanjie Li; et al. (Frontiers Media S.A., 2022)
Long interspersed nuclear element 1 (LINE-1) is a dominant autonomous retrotransposon in human genomes which plays a role in affecting the structure and function of somatic genomes, resulting in human disorders including genetic disease and cancer. LINE-1 encoded ORF1p protein which possesses RNA-binding and nucleic acid chaperone activity, and interacts with LINE-1 RNA to form a ribonucleoprotein particle (RNP). ORF1p can be detected in many kinds of tumors and its overexpression has been regarded as a hallmark of histologically aggressive cancers. In this study, we developed an In-Cell Western (ICW) assay in T47D cells to screen the compounds which can decrease the expression of ORF1p. Using this assay, we screened 1,947 compounds from the natural products library of Target Mol and Selleckchem, among which three compounds, Hydroxyprogesterone, 2,2':5',2"-Terthiophene and Ethynyl estradiol displayed potency in diminishing LINE-1 ORF1p expression level. Further mechanistic studies indicated the compounds act by affecting LINE-1 RNA transcription. Notably, we demonstrated that the compounds have an inhibitory effect on the proliferation of several lung and breast cancer cell lines. Taken together, we established a high throughput screening system for ORF1p expression inhibitors and the identified compounds provide some clues to the development of a novel anti-tumor therapeutic strategy by targeting ORF1p.